APPLICATION OF EVERYONE IS A TEACHER HERE LEARNING MODEL TO IMPROVE SELF CONFIDENCE STUDENTS - Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
This research is motivated by some students problems about the belief in its ability. This is based on early observation of one-way learning so that students are not used to speaking in front of many people. One of the efforts is to improve self-confidence by applying the learning model of everyone is a teacher here. The objectives to be achieved in this research are: (1) to express the implementation of learning by applying the learning model of everyone is a teacher here to improve student self confidence, (2) To express the improvement of self confidence of students after applying the learning model of everyone is a teacher here. This study is a classroom action research adapted from the Kemmis and Mc model. Taggart. This research was conducted in Grade 4 which amounted to 30 students. The results obtained from the learning process has progressed from cycle I to cycle II. Negative findings found in cycle I amounted to 10, while negative findings in cycle II amounted to two. From the data it is recommended to teachers to use the learning model of everyone is a teacher here to improve student self confidence.